Free-standing GaN grating couplers and rib waveguide for planar photonics at telecommunication wavelength. (1st January 2018) - Liu, Qifa; Wang, Wei
Highlights: Silicon based GaN planar photonics at telecommunication wavelength is proposed. The planar photonics structure featured air-cladding and controllable thickness. The device is fabricated by double-side process combining single-step process. Shallow etched 1D uniform groove coupling light into waveguide with optimal 5 dB loss. The resonance peaks attributes to F-P cavity of high contrasts refractivity. Abstract: Gallium Nitride (GaN) free-standing planar photonic device at telecommunication wavelength based on GaN-on-silicon platform was presented. The free-standing structure was realized by particular double-side fabrication process, which combining GaN front patterning, Si substrate back releasing and GaN slab etching. The actual device parameters were identified via the physical characterizations employing scanning electron microscope (SEM), atomic force microscope (AFM) and reflectance spectra testing. High coupling efficiency and good light confinement properties of the gratings and rib waveguide at telecommunication wavelength range were verified by finite element method (FEM) simulation. This work illustrates the potential of new GaN photonic structure which will enable new functions for planar photonics in communication and sensing applications, and is favorable for the realization of integrated optical circuit.